Developmental Fluoxetine Exposure Alters Behavior and Neuropeptide Receptors in the Prairie Vole - Lawrence, Rebecca H.; Palumbo, Michelle C.; Freeman, Sara M.; Guoynes, Caleigh D.; Bales, Karen L. (Frontiers in Behavioral Neuroscience, 2020)
Developmental exposure to selective serotonin reuptake inhibitor (SSRI) increases the risk of Autism Spectrum Disorder (ASD); however, the underlying neurobiology of this effect is not fully understood. Here we used the socially monogamous prairie vole as a translational model of developmental SSRI exposure. Paired female prairie voles (n=20) were treated with 5mg/kg subcutaneous fluoxetine (FLX) or saline (SAL) daily from birth of the second litter until the day of birth of the 4th litter. This design created three cohorts of fluoxetine exposure: postnatal exposure in litter 2, both prenatal and postnatal exposure in litter 3, and prenatal exposure in litter 4. Post-weaning, subjects underwent behavioral testing to detect changes in sociality, repetitive behavior, pair-bond formation, and anxiety-like behavior. Quantitative receptor autoradiography was performed for oxytocin, vasopressin 1a, and serotonin 1a receptor density in a subset of brains. We observed increased anxiety-like behavior and reduced sociality in developmentally FLX exposed adults. FLX exposure decreased oxytocin receptor binding in the nucleus accumbens core and central amygdala, and vasopressin 1a receptor binding in the medial amygdala. FLX exposure did not affect serotonin 1A receptor binding in any areas examined. Changes to oxytocin and vasopressin receptors may underlie the behavioral changes observed and have translational implications for the mechanism of the increased risk of ASD subsequent to prenatal SSRI exposure.